Circuit, technological, physical and topological methods improve performance integral comparator - Новосядлий, Степан Петрович (Eastern-European Journal of Enterprise Technologies, 2014)
Performance comparators defined as circuit solutions and topological and technological improvements. This article aims to study existing integrated comparators, which held copyright modernization circuitry, topologies and technologies that improve their performance at least 2 times, which determines the feasibility of the article. As a result of investigations by the original Schematic technological solutions to improve performance integrated comparators. Its input stage must have high attenuation of common-mode component and the ability to withstand large common-mode and differential input signals which are not saturating, ie not getting into profiles from which the comparator will go long. These solutions are implemented with technology integrated comparators as on mono-Si, and the gallium arsenide and thereby increase the reliability of integrated circuits and simplify the production process. Such studies will be useful in the construction of high-speed VLSI structures where elements act as analogue and digital comparators.